Apathy in rapid eye movement sleep behaviour disorder is common and under-recognized. - Barber, T; Muhammed, K; Drew, D; Lawton, M; Crabbe, M; Rolinski, M; Quinnell, T; Zaiwalla, Z; Ben-Shlomo, Y; Husain, M; Hu, M (Wiley, 2017)
Background Apathy is an important neuropsychiatric feature of Parkinson’s disease (PD), which often emerges before the onset of motor symptoms. Patients with rapid eye movement sleep behaviour disorder (RBD) have a high probability of developing Parkinson’s disease in future. Neuropsychiatric problems are common in RBD, but apathy has not previously been detailed in this key prodromal population. Methods 88 patients with polysomnographically proven RBD, 65 patients with PD and 33 controls were assessed for apathy using the Lille Apathy Rating Scale (LARS). Cognition and depression were also quantified. The sensitivity of the Unified Parkinson’s Disease Rating Scale screening questions for apathy and depression was calculated. Results 46% of Patients with RBD were apathetic, compared with 31% of Parkinson’s patients in our sample. Most RBD patients with depression were apathetic but more than half of apathetic patients were not depressed. The sensitivity of the single UPDRS screening question was only 33% for mild apathy and 50% for severe apathy. Conclusions Apathy is common in RBD and is underestimated by a single self-report question. Recognition of apathy as a distinct neuropsychiatric feature in RBD could aid targeted treatment interventions and might contribute to understanding of prodromal Parkinson’s disease.